Does China’s poverty alleviation policy improve the quality of the ecological environment in poverty-stricken areas? - Ran, Rong; Ni, Zhengxing; Hua, Lei; Li, Tingrou (Frontiers in Environmental Science, 2022)
Poverty eradication and environmental protection as the two global goals of sustainable development. China's poverty alleviation policy attempts to achieve green development in poverty-stricken areas by eliminating poverty while also promoting environmental protection. Since the Poverty-stricken counties on the Qinghai-Tibet Plateau also have the dual attributes of ecological degradation and ecological fragility, it is of great significance to study the impact of poverty alleviation policy on their environment. In this research, taking poverty alleviation policy as the entry point, Based on panel data and Remote Sensing Ecological Index (RSEI) for poverty-stricken counties on the Qinghai-Tibet Plateau from 2011-2019, and using the Differences-in-Differences (DID) method to verify the impact of policy on environmental quality. The main findings of the study were:(1) The poverty alleviation policy has a significant improvement effect on the ecological environment quality of counties in the Qinghai-Tibet Plateau region, and this conclusion still holds in a series of robustness tests using methods including the changing sample size method and the variable replacement method. Moreover, the policy effect has a certain time lag and its effect persists in the long term; (2) It is mainly due to the increased level of government public expenditure and the easing of government financial pressure that has contributed to the improvement of environmental quality in poverty-stricken areas.;(3) Policy heterogeneity suggests that industrial poverty eradication policies are more conducive to promoting synergistic economic and environmental development in poverty-stricken areas.